The ITO thin films deposited by magnetron sputtering for solar cell applications - Szindler, Marek; Szindler, Magdalena M.; Lukaszkowicz, Krzysztof; Matus, Krzysztof; Nosidlak, Natalia; Jaglarz, Janusz; Fijałkowski, Mateusz; Nuckowski, Paweł (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The paper presents the results of research on the surface topography and electrical properties of ITO thin films deposited by PVD for applications in silicon photovoltaic cells. The surface condition and chemical composition were characterized using a scanning electron microscope and the thickness and optical constants were measured using a spectroscopic ellipsometer. To compare the impact of the preparation process on the properties of layers, deposition was carried out at three different temperatures: 25, 200, and 400◦C. As the temperature increased, the surface roughness changed, which correlated with the results of structural tests. The crystallite size increased from 11 to 46 nm. This, in turn, reduced the surface resistance. The electrical properties were measured using a four-point probe method and then the prepared solar cells containing ITO thin films in their structure were examined. By controlling the deposition parameters, the surface resistance of the deposited layer (26 Ohm/✷) and the efficiency of the prepared solar cells (18.91%) were optimized. Currently, ITO has the best properties for use in optoelectronics and photovoltaics among the known TCO layers. The magnetron sputtering method is widely used in many industries. Therefore, the authors predict that TCO layers can replace currently used antireflection layers and reduce the number and dimensions of front metal contacts in solar cells.